Čustveni vidiki pri izbiri jezikovnega koda slovenskih literarnih ustvarjalcev v Italiji - Cergol, Jadranka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
The article explores the choice of language code among Slovene writers in Italy. During the last decade, there has been a shift in the choice of language, just like among Slovenes in Austrian Carinthia, as some writers choose to write either in their second language or language of the environment or opt for bilingual or translingual writing. In the article, the author connects this phenomenon with psycholinguistic theories on the emotional aspects of language code choice, proving that there are different levels of emotional experience of language, which of course is influenced by very different (both internal and external) factors. Since there are many responses to the literary multilingual phenomenon and because the authors themselves justify their choice in various forms, the article attempts to frame and explain it based on the findings of the psychology of multilingual speakers on the example of Slovene writers in Italy.
Keywords: bilingual writers; choice of language code; čustveni vidiki; dvojezičnost; emotional aspects; Italija; Italy; izbira jezikovnega koda; Slovenci v Italiji; Slovene minority; Slovenes in Italy; slovenska manjšina; slovenski književniki